A study of conditional expectation on filtered fermionic Fock space - Ahmad, Zulaihatu Tijjani; Tijjani, Abba Ali (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This paper presents a structural analysis of stopping time in noncommutative probability theory within the context of Fermionic Fock Space. In particular, the construction of conditional expectation and the introduction and analysis of stopping times on an antisymmetric Fock space are undertaken using an increasing full right continuous filtered antisymmetric Fock Space. The conditional expectation on the filtered Fock space is demonstrated to be completely positive.